Assessment for lead contamination and its effect on escherichia coli in muscovado sugar - Dollete, Una Grace Maestrado
The quality of muscovado sugar randomly sampled in the markets of San Jose, Antique was evaluated for the presence of lead contamination and its possible effect on pathogens that might be present, specifically E. coli.